Literature Review: Quality of Life in Patients with Overactive Bladder - Vitaria Wahyu Astuti; Ayu Ratantri; Sandy Kurniajati (STIKes Patria Husada Blitar, 2022)
Overactive Bladder, hereinafter referred to as OAB, is a complaint of urgency accompanied by urgency incontinence or without urgency incontinence, which is usually followed by an increase in urinary frequency during the day and nocturia, without infection or other pathology of the bladder. OAB can affect the quality of life of sufferers. This study analyzes the relationship between OAB and quality of life based on databases such as Science Direct, Elsevier, Willey Library, Sage Journal, and Google Scholar, 2010-2020. The study results show that the prevalence of OAB in men and women increases with age and women are at greater risk major have OAB. The incidence of OAB is most experienced at the age of > 60 years. Based on 10 journals, 6 journals stated that there was a relationship between OAB and quality of life. The conclusion of this study is that OAB can reduce the quality of life in men and women